Research on the Characteristics of High-Performance Textured Ceramic Materials and Their Application in Composite Rod Transducers - Fenghua Tian; Yiming Liu; Wenqiang Tian; Lei Wang; Baoan Hao; Shuai Yang (Actuators)
Recently, textured piezoelectric ceramics have become a hot topic in the field of piezoelectric materials. Due to their high cost-effectiveness, textured ceramics are expected to be the material of choice for the next generation of acoustic transducers. In this study, we investigated the coercive field (Ec), piezoelectric constant (d33), and dielectric constant (ε33) of textured PIN-PSN-PT ceramics under different torques, in response to the demand for the development of composite rod transducer technology for transmitting and receiving. Based on the obtained data, a wideband composite rod transducer was designed and fabricated using textured PIN-PSN-PT ceramics with high performance. Compared with conventional PZT piezoelectric ceramic transducers of the same size, the wideband composite rod transducer made with textured ceramics extends the frequency band to a lower frequency of 6.5 kHz, improves the emission performance by 2 dB, and enhances the reception performance by 2 dB. Compared with conventional PZT piezoelectric ceramics in the same frequency band, the acoustic performance is comparable, but there is a volume reduction of 59.23% and a weight reduction of 49.7%, solving the technical bottleneck of developing composite rod transducers that are miniaturized and lightweight. The research results of this study have important reference value for the engineering application of textured ceramic materials in acoustic transducers.